2020
DOI: 10.3390/pr8091085
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bioadsorption of Cd2+ Ions: Adsorption Isotherms, Mechanism, and an Insight to Mycoremediation

Abstract: The objective of this paper is to establish the significance of the mycoremediation of contaminants such as Cd2+ to achieve sustainable and eco-friendly remediation methods. Industries such as electroplating, paint, leather tanning, etc. release an enormous amount of Cd2+ in wastewater, which can drastically affect our flora and fauna. Herein, we report on the in vitro bioadsorption of Cd2+ ions using fungal isolates obtained from different contaminated industrial sites. The detailed studies revealed that two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Hence, fungi were acting as a potential bioremediating agent. Several filamentous fungi, such as Trichoderma, Penicillium, Aspergillus flavus, A. niger, and A. fumigatus, were used to remove heavy metal ions from contaminated water (Joshi et al, 2011;Kumar et al, 2020;Vaksmaa et al, 2023). Recent advances in nanoscience and technology have paved the way for the development of better wastewater treatment strategies.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Hence, fungi were acting as a potential bioremediating agent. Several filamentous fungi, such as Trichoderma, Penicillium, Aspergillus flavus, A. niger, and A. fumigatus, were used to remove heavy metal ions from contaminated water (Joshi et al, 2011;Kumar et al, 2020;Vaksmaa et al, 2023). Recent advances in nanoscience and technology have paved the way for the development of better wastewater treatment strategies.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Previous studies have proved that microorganisms isolated from the contaminated sites showed high resistance toward pollutants and hence better pollution remediation potential [39,40]. In fact, for an effective bioremediation approach it is important to have bacterial strains that combine a high resistance property and ability to reduce Cr(VI) [7].…”
Section: Cr Reduction Ability Of the Cr-resistant Isolate Strainsmentioning
confidence: 99%
“…Adsorption is another strategy of mycoremediation. For example, the removal of heavy metal pollutants can be achieved by adsorption [23,24].…”
Section: Introductionmentioning
confidence: 99%